Efforts to improve mathematics learning outcomes through the project based learning model for class x students of smk negeri 1 hilimegai - Marinus Ndruru (Institute of Accounting Research and Novation (IARN), 2023)
The aim of this research is to improve student learning outcomes in the cognitive and psychomotor domains through the application of the Project Based Learning learning model. The type of research is classroom action research (PTK). The PTK model used is the C. Kemmis & Mc Taggart spiral model which is implemented in 2 cycles. Data collection techniques are test techniques and non-test techniques. The research instrument uses test items and observation sheets. The data analysis technique used is descriptive comparative. Based on the research results, it shows that the cognitive domain mathematics learning outcomes based on the percentage of pre-cycle, cycle I and cycle II learning completion are 20.8%; 54.2%; 91.8%. Meanwhile, the results of mathematics learning in the psychomotor domain based on the percentage of learning completion in pre-cycle, cycle I and cycle II were 41.6%; 70.8%; 95.8%. Thus, the application of the Project Based Learning model can improve student learning outcomes in the cognitive and psychomotor domains of Class X students at SMK Negeri 1 Hilimegai.